Development of a negative pressure hood for isolation and transportation of individual patient with respiratory infectious disease - Limei Hao; Jinhui Wu; Jinming Zhang; Zhangyi Liu; Ying Yi; Zongxing Zhang; Enlei Zhang; Jiancheng Qi (Elsevier, 2019)
The frequent and sudden occurrence of both known and unknown infectious diseases can cause global social panic. If the source of infection can be effectively controlled in the early stages of an outbreak, the spread of infectious diseases can be prevented. In view of this situation, this study developed for infectious or suspected infectious patients a negative pressure isolation hood which effectively achieves direct individual isolation during the early stages of disease outbreak, and facilitates long-distance transport. The hood body is made of flexible transparent polyvinyl chloride (PVC) material, and the combination of the hood material is airtight. The unique inflatable column support structure and the design of the inflatable neck sleeve effectively ensure both stiffness and air tightness of the hood body. The electrical exhaust system maintains a stable negative pressure environment inside the hood, and polluted air inside the hood can be purified by a high efficiency filter. Test results showed that the internal noise of the hood was 68 ± 1 dB (A), the air exhaust volume of the electric exhaust system was not <200 L/min, and the filtration efficiency of the filter to 0.3 μm particles was >99.99%, indicating that the hood achieved effective isolation protection for patients with respiration infectious diseases.